2001
DOI: 10.1097/00008571-200108000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic characterization of young normotensive men carrying the 825T-allele of the G-protein ß3 subunit

Abstract: A C825T polymorphism was recently identified in the gene for the G-protein beta3 subunit, the T-allele being associated with hypertension. To better understand the underlying pathophysiological mechanisms, we compared the haemodynamics of young healthy males with and without the T-allele. In three studies, subjects were investigated with regard to cardiac and vascular function at rest and following intravenous administration of the beta-adrenoceptor antagonist, propranolol, and the alpha2-adrenoceptor agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
4
22
3
Order By: Relevance
“…26 In population studies, the C825T variant has been variably associated with increased risk of hypertension, atherosclerosis, myocardial infarction, and stroke. 15 Although GNB3 genotype did not affect the vasoconstricting effect of peripherally acting ␣ 2 -agonists, mediated by vascular ␣ 2 -receptors, 27 the sympathoinhibitory response to the centrally acting ␣ 2 -agonist clonidine differed by GNB3 genotype: In keeping with the in vitro findings, a study in 30 White Europeans found that clonidine reduced blood pressure, total peripheral resistance, and plasma norepinephrine concentrations significantly more in carriers of the T825 allele than in noncarriers. 4 Our study included a similar number of C allele homozygotes and 4 times as many carriers of the T allele, and found no genotype effect on the centrally mediated dexmedetomidine responses.…”
Section: Discussionmentioning
confidence: 70%
“…26 In population studies, the C825T variant has been variably associated with increased risk of hypertension, atherosclerosis, myocardial infarction, and stroke. 15 Although GNB3 genotype did not affect the vasoconstricting effect of peripherally acting ␣ 2 -agonists, mediated by vascular ␣ 2 -receptors, 27 the sympathoinhibitory response to the centrally acting ␣ 2 -agonist clonidine differed by GNB3 genotype: In keeping with the in vitro findings, a study in 30 White Europeans found that clonidine reduced blood pressure, total peripheral resistance, and plasma norepinephrine concentrations significantly more in carriers of the T825 allele than in noncarriers. 4 Our study included a similar number of C allele homozygotes and 4 times as many carriers of the T allele, and found no genotype effect on the centrally mediated dexmedetomidine responses.…”
Section: Discussionmentioning
confidence: 70%
“…There are no previous studies on the associations between the GNB3 C825T genotype and submaximal exercise hemodynamic phenotypes. However, Schafers et al (30) reported an elevated resting stroke volume and a greater fall in resting stroke volume in response to acute administration of propranolol, a ␤-adrenoceptor antagonist, in healthy young men carrying the GNB3 825T allele compared with the CC homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that dexmedetomidine resulted in dose-dependent venoconstriction in the hand vein model, with a maximum of approximately 75%, which is greater than the maximum responses reported with clonidine (27% to 54%) 15,16,21 and the more specific ␣ 2 -AR agonist, azepexol (52% to 68%). 16,22 The sensitivity to dexmedetomidine among individuals varied considerably, resulting in a Ͼ1000-fold range in ED 50 . However, venous sensitivity in blacks and whites did not differ, indicating that increased ␣ 2 -AR sensitivity in blacks is unlikely to explain our previous observation that the reduction in blood pressure after clonidine was attenuated in blacks.…”
Section: Muszkat Et Al Ethnicity and Vascular ␣ 2 -Adrenoceptor Responsementioning
confidence: 99%